2014
DOI: 10.1002/eat.22333
|View full text |Cite
|
Sign up to set email alerts
|

Using ecological momentary assessment to examine interpersonal and affective predictors of loss of control eating in adolescent girls

Abstract: Objective Pediatric loss of control (LOC) eating is predictive of partial- and full-syndrome binge eating disorder. The interpersonal model proposes that LOC eating is used to cope with negative mood states resulting from interpersonal distress, possibly on a momentary level. We therefore examined temporal associations between interpersonal problems, negative affect, and LOC eating among overweight adolescent girls using ecological momentary assessment (EMA). Method Thirty overweight and obese (≥85th body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 45 publications
(107 reference statements)
4
80
3
Order By: Relevance
“…19 The interpersonal model proposes that hyperphagia associated with LOC episodes may reflect a response to negative affective states induced by interpersonal conflicts. 19 Our data from retrospective self-reports 20 and ecological momentary assessment in the natural environment 21 generally support this theoretical model in youth.…”
Section: Introductionsupporting
confidence: 72%
“…19 The interpersonal model proposes that hyperphagia associated with LOC episodes may reflect a response to negative affective states induced by interpersonal conflicts. 19 Our data from retrospective self-reports 20 and ecological momentary assessment in the natural environment 21 generally support this theoretical model in youth.…”
Section: Introductionsupporting
confidence: 72%
“…This is consistent with research indicating that negative affect is associated with LOC eating. 9,26 The coping, self-evaluation, and mindfulness skills taught in LIBER8, as well as the attention to examples involving food-related situations, might have made participants more aware of their eating habits and provided tools to improve these behaviors. For the 2BFit group, the structure and focus on nutrition and physical activity seems to have also made participants more aware of their maladaptive eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…25 Research supports this model, identifying associations among interpersonal problems, negative affect, and LOC eating. 9,26 Moreover, BE is associated with deficits in emotion regulation skills, 9,27 suggesting that interventions emphasizing coping strategies might prove especially effective in treating this problematic eating behavior. 9,28 …”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, while the laboratory has the advantage of controlling the exact conditions under which eating behavior is observed, it is also possible that other stressors that induce state negative affect may impact adolescents’ EAH to a greater extent in their natural environments and that the most significant sources of stress differ individual-to-individual (Redlin, Miltenberger, Crosby, Wolff, & Stickney, 2002). For example, ecological momentary assessment studies indicate that cognitions and emotions associated with food, eating, body image (Hilbert, Rief, Tuschen-Caffier, de Zwaan, & Czaja, 2009), and interpersonal conflict (Ranzenhofer, et al, 2014; Shingleton, et al, 2013) frequently precede disinhibited eating episodes in youth. Thus, a task for future research may be to consider how to use experimental paradigms to evaluate stressors more salient to specific youth at-risk for food disinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a task for future research may be to consider how to use experimental paradigms to evaluate stressors more salient to specific youth at-risk for food disinhibition. Studies of self-reported disinhibited eating behavior in the natural environment frequently characterize negative affect as a single construct (Berg, et al, 2014; Heron, Scott, Sliwinski, & Smyth, 2014; Ranzenhofer, et al, 2014), and there may be meaningful differences in depressed versus stressed affect, for example. Whether the intensity of a specific emotional experience has an influence on energy intake is also an important area of future research.…”
Section: Discussionmentioning
confidence: 99%